Uncovering the optimal corporate social responsibility bearer in express packaging waste management system considering consumer surplus and echelon utilization - Yang, Jiahui (Waste management (New York, N.Y.), 2025)
Copyright © 2025 Elsevier Ltd. All rights reserved.